Effects of repeated cryostimulation exposures on sleep quality in swimmers during an intense training period - Arc-Chagnaud, C.; Dugué, B.; Pla, R.; Bouzigon, R.; Bosquet, L.; D-Day Consortium; Dupuy, O. (Experimental Physiology, 2025)
The aim of this study was to evaluate the effects of daily partial body cryostimulation exposures on sleep and recovery parameters in elite swimmers undergoing an intense training period. Twenty-three elite French swimmers (7 females and 16 males) were involved in this controlled cross-over protocol. The experiment took place during 2 weeks of intense training load. Each week (5 days and 5 nights) represented one of the two experimental conditions: partial body cryostimulation exposures (CRYO) or control sessions (CONT). Daily partial body cryostimulation exposure of 3 min at -110°C was performed (or not) during a consecutive period of 5 days, after the evening training session. Perceived wellness (anxiety, tiredness, depression and mood profile), sleep quality (via actimetry and cerebral recording) and nocturnal heart rate variability were evaluated. Collection of saliva samples permitted the measurement of C-reactive protein and melatonin. Perceived anxiety, tiredness and depression were reduced after the CRYO week, concomitant with an improved mood profile. Recordings of cerebral activity during the night highlighted increased slow-wave sleep duration in the first sleep cycle during the CRYO week. Other sleep parameters, including total sleep time, sleep latency, efficiency or movements during the night, remained unchanged. The concentration of C-reactive protein in saliva was lower during the CRYO week compared with the CONT week. Moreover, sleep analysis allowed a distinction between better sleepers and poor sleepers. In the latter group, only poor sleepers among the male swimmers obtained a benefit on their sleep from cryotherapy. Repeated cryostimulation exposures during 1 week of intense training improved perceived wellness in elite swimmers, reduced inflammation, and modulated sleep architecture by increasing slow-wave sleep duration.